Outcomes of Patients Suspended From the National Kidney Transplant Waiting List in the United Kingdom Between 2000 and 2010. Issue 8 (August 2020) - Wallace, David; Robb, Matthew; Hughes, Winter; Johnson, Rachel; Ploeg, Rutger; Neuberger, James; Forsythe, John; Cacciola, Roberto
Abstract : Background: In the United Kingdom, 1 in 3 patients on the National Kidney Transplant Waiting List (NKTWL) is suspended from the list at least once during their wait. The mortality of this large cohort of patients remains underreported and poorly described. Methods: We linked patient records from the UK transplant registry to mortality data from the Office of National Statistics and evaluated the impact of a clinically induced suspension event by estimating hazard ratios (HRs) that compared mortality and graft survival between those who had experienced a suspension event and those who had not. Results: Between January 1, 2000, and December 31, 2010, 16.7% (2221/13 322) of all patients registered on the NKTWL were suspended. Forty-eight percent (588/1225) of those who were suspended and who were never transplanted died, most often from cardiothoracic causes. A suspension event was associated with increased mortality from the time of listing (adjusted HR [aHR], 1.79; 1.64-1.95) and from the time of transplantation (aHR, 1.20; 1.06-1.37; P = 0.005). Graft survival was also poorer in those who had been suspended (aHR, 1.13; 1.01-1.28; P = 0.04). Conclusions: Patients suspended on the NKTWL have a significantly higher rate of mortality both on the waiting list and following transplantation. Earlier prioritization of patients at risk of experiencing a suspension event may improve their outcomes. Abstract : Supplemental Digital Content is available in the text.